with Jasanoff, Jay H. - Ives Goddard, R. H., Indo-European Studies - Watkins, Calvert (1972)
Special Report to the National Science Foundation. Report HARV-LING-01-72, multilith; S. 4-230 enthält viel über Hethitisch und Palaisch.